2000
DOI: 10.1114/1.1326032
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Activity in Ventricular Cells Induced by Early Afterdepolarizations Developed in Purkinje Cells

Abstract: The development of early afterdepolarizations (EADs) in Purkinje fibers and their propagation to ventricular muscle cells are studied by computer modeling. The Purkinje-ventricular system has been simulated by a two-dimensional model of a Purkinje fiber (PF) connected to a thin sheet of ventricular muscle tissue (VMT). EADs are induced in the PF by enhancing the fast second inward current, iCa,f, and blocking the delayed K+ current, iK, while the VMT is kept under physiological conditions. Different phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…This can be thought of as a premature stimulus coming from the Purkinje fiber. 31 Our main result is summarized in Fig. 9 where we show the length of reentry, measured in seconds, as a function of the two geometry parameters, w and r, for fixed long QT syndrome strength µ = 0.08.…”
Section: Two Dimensionsmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be thought of as a premature stimulus coming from the Purkinje fiber. 31 Our main result is summarized in Fig. 9 where we show the length of reentry, measured in seconds, as a function of the two geometry parameters, w and r, for fixed long QT syndrome strength µ = 0.08.…”
Section: Two Dimensionsmentioning
confidence: 98%
“…42 Under this condition, numerical simulations have revealed that the inclusion of a large resistive barrier between the Purkinje fibers and the ventricular cells can lead to early after depolarizations in the Purkinje fibers that are able to generate extra stimuli in the ventricular domain. 31 Our numerical simulations were carried out using a simplified transmural geometry of the ventricular wall that consisted of a centrally located M cell domain, sandwiched between two electrophysiologically equal domains representing the endo-and epicardium. Incorporating more realistic geometries and endo-and epicardial cells with different electrophysiological properties, however, will most likely not change the qualitative conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…NS was kept under normal physiological conditions while AS was set under conditions that favor the induction of EADs (figure 1). The generation of EADs is favored by conditions that lengthen action potential duration (APD), such as conditions that increase an inward current or decrease an outward current [8]. We blocked the components of the delayed rectifier K + current, I Kr and I Ks, in the range from 0% to 100% while the L-type Ca 2+ current (I caL ) was incremented to 100% in order to probe different EAD conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Early afterdepolarizations (EADs) are subthreshold depolarizations that occur in phases 2 and 3 of the action potential (AP), causing interruption or delay in repolarization [6][7][8]. January et al suggested that induction of EADs require the prolongation of the action potential plateu and the recovery of the L-type calcium current (I CaL ) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation